Temporal expression of bacterial proteins instructs host CD4 T cell expansion and Th17 development. - Seung-Joo Lee; James B McLachlan; Jonathan R Kurtz; Danhua Fan; Sebastian E Winter; Andreas J Baumler; Marc K Jenkins; Stephen J McSorley (PLoS Pathogens)
Pathogens can substantially alter gene expression within an infected host depending on metabolic or virulence requirements in different tissues, however, the effect of these alterations on host immunity are unclear. Here we visualized multiple CD4 T cell responses to temporally expressed proteins in Salmonella-infected mice. Flagellin-specific CD4 T cells expanded and contracted early, differentiated into Th1 and Th17 lineages, and were enriched in mucosal tissues after oral infection. In contrast, CD4 T cells responding to Salmonella Type-III Secretion System (TTSS) effectors steadily accumulated until bacterial clearance was achieved, primarily differentiated into Th1 cells, and were predominantly detected in systemic tissues. Thus, pathogen regulation of antigen expression plays a major role in orchestrating the expansion, differentiation, and location of antigen-specific CD4 T cells in vivo.